PARTISIPASI ANGGOTA DALAM KEGIATAN KELOMPOK TANI MASAWANGAN DI KELURAHAN TARA-TARA DUA KECAMATAN TOMOHON BARAT - Merry Ema Mentang; Welson Marthen Wangke; Benny Adrian Berthy Sagay (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the participation of members in the Masawangan farmer group activities in Taratara Dua Village, West Tomohon District. The study was conducted in September to November 2019. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with respondents and secondary data obtained from government agencies related to the research topic. Sampling in this study was carried out by census technique that is all members of the Masawangan Farmer Group, totaling 10 respondents so that all members were interviewed using a questionnaire. Analysis of the data used in this research is descriptive analysis using a Likert Scale. The results showed that the participation of members in the planning, implementation and evaluation stages of the Masawangan farmer group was high.*eprm*